2021
DOI: 10.3389/fphys.2021.714846
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Polysaccharides on the Epithelial Barrier Function in Intestinal Mucositis

Abstract: Intestinal mucositis is a clinically relevant side effect of anticancer therapies. It is experienced by 60–100% of patients undergoing treatment with high doses of chemotherapy, radiation therapy, and bone marrow transplantation. Intestinal mucositis can manifest as pain, weight loss, inflammation, diarrhea, rectal bleeding, and infection; affecting normal nutritional intake and intestinal function. It often impacts adherence to anticancer therapy as it frequently limits patient’s ability to tolerate treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…Epithelial barrier dysfunction is a characteristic and pathological mechanism of airway inflammation in asthma patients (Georas and Rezaee, 2014 ). In comparison to non-asthmatic patients, the bronchial epithelial barrier function in asthmatic patients is impaired (Inoue et al, 2020 ), making it easier for pathogens or allergens to enter the airway tissue, activating an immune response, and leading to asthma exacerbation (da Silva, 2021 ). Richards et al ( 2020 ) demonstrated that propionate and butyrate can enhance the barrier function of human bronchial epithelial cells and restore the impaired barrier function induced by stimulation with IL-4, IL-13, and dust mite extract.…”
Section: Relationship Between Gut Microbiome and Susceptibility To As...mentioning
confidence: 99%
“…Epithelial barrier dysfunction is a characteristic and pathological mechanism of airway inflammation in asthma patients (Georas and Rezaee, 2014 ). In comparison to non-asthmatic patients, the bronchial epithelial barrier function in asthmatic patients is impaired (Inoue et al, 2020 ), making it easier for pathogens or allergens to enter the airway tissue, activating an immune response, and leading to asthma exacerbation (da Silva, 2021 ). Richards et al ( 2020 ) demonstrated that propionate and butyrate can enhance the barrier function of human bronchial epithelial cells and restore the impaired barrier function induced by stimulation with IL-4, IL-13, and dust mite extract.…”
Section: Relationship Between Gut Microbiome and Susceptibility To As...mentioning
confidence: 99%
“…In addition, in recent years, natural products including Chinese herbal medicines have displayed distinct clinical outcomes in managing chemotherapy-induced side effects including gut mucositis, nausea and vomiting [103][104][105], and some of them have been verified in animal experiments, such as Wuzi Yanzong Pills [106], Shengjiang Xiexin decoction [107], Gegen Qinlian decoction [108], Qingjie Fuzheng Granule [109], Amomi Fructus [110], Steamed rehmannia root [111], Patchouli [27,112], Saikosaponin-A [7], Aquilaria agallocha [113] and Andrographolide [114], with the underlying mechanisms of action involving antioxidation, anti-inflammation and anti-apoptosis. In addition, some ingredients extracted from Crassostrea hongkongensis [55], Dendrobium sonia [115], Dendrobium huoshanense [116], Schisandrae chinensis [117], Salvia miltiorrhiza [118], Scutellaria baicalensis [119], and Pogostemon cablin [27] are likely to regulate gut microbiota through promoting the proliferation of commensal microbiota and inhibiting pathogenic bacteria.…”
Section: Prophylactic Effect Of Antibiotics Probiotics and Natural Productsmentioning
confidence: 99%
“…6 To achieve this goal, prebiotic polysaccharides can regulate inflammatory/immune responses, attenuate oxidative stress and promote intestinal mucosa integrity by regulating mucin production and increasing the expression of various tight junction molecules. 7 Gracilariopsis lemaneiformis is a red alga that holds significant economic value because it can be directly consumed or processed into various products, including food supplements, cosmetics and medicines. The alga is rich in polysaccharides, phycobiliproteins, pigments and other nutrients and functional components, of which polysaccharides are the primary active components.…”
Section: Introductionmentioning
confidence: 99%
“…Among these interventions, prebiotic polysaccharides have been found to play a crucial role in protecting against chemotherapy‐induced intestinal damage 6 . To achieve this goal, prebiotic polysaccharides can regulate inflammatory/immune responses, attenuate oxidative stress and promote intestinal mucosa integrity by regulating mucin production and increasing the expression of various tight junction molecules 7 …”
Section: Introductionmentioning
confidence: 99%